(untitled) (Herald of Journalism, 2020)
The last years existence of the USSR were characterized by further ac- cumulation of economic and social problems that couldn’t but affect and national life of the people which were its part. Sharp decrease in rates of economic development and social corrosion of the society led by party into an ideologichky blind alley testified that the country is in a pre-crisis state. First of all, this insolvency has an effect on the sphere of national development and the international relations. Therefore need the deep analysis research of common problems of the republic, including activity of domestic journalism.